The Relationship Between Supply Chain Strategies and Supply Chain Responsiveness among Manufacturing Industries in Selangor, Malaysia - Lim, Yee Lin; Kamaruddin, Nor Kamariah (Research in Management of Technology and Business, 2025)
The manufacturing sector plays a crucial role in Malaysia’s economy, contributing significantly to the country’s Gross Domestic Product (GDP). However, manufacturing industries face challenges in maintaining supply chain responsiveness due to issues such as late raw material deliveries, production delays, and inefficient collaboration with suppliers. Therefore, the research aims to identify the level of supply chain responsiveness, the level of supply chain strategies, and the relationship between these variables. A quantitative approach was applied, using a survey questionnaire distributed to 317 managerial-level employees in manufacturing companies, with only 257 valid responses. The data was analyzed using Statistical Package for Social Sciences (SPSS) software, which included descriptive and Spearman’s correlation analysis. The results indicated that lean supply chain, agile supply chain, strategic supplier partnerships, and postponement strategies were implemented at a high level, with agile supply chain strategy showing the strongest influence on supply chain responsiveness. The analysis revealed that supply chain responsiveness (operations system, logistics process, and supplier network responsiveness) were positively correlated with the supply chain strategies. These findings suggest that adopting comprehensive supply chain strategies can significantly enhance the ability of manufacturing industries to respond to market demands and uncertainties. The study contributes to the body of knowledge on supply chain strategy and supply responsiveness, providing a valuable reference for future researchers interested in this field. Additionally, it offers practical insights for supply chain managers aiming to strengthen supplier collaboration, optimize inventory management, and improve operational efficiency, thereby enhancing overall performance and competitiveness in the global market.